Is there a connection between children's language skills, creativity, and play?. Issue 8 (11th June 2022) - Holmes, Robyn M.; Kohm, Kristen; Genise, Samantha; Koolidge, Louis; Mendelson, Drew; Romeo, Lynn; Bant, Christine
ABSTRACT: This study explored the connection between children's language skills, creativity, and play. The participants were 151 (76 boys and 75 girls) primarily middle-income, European American children. Ages ranged from 4 to 6 years. This project employed mixed methods approaches. Children engaged in several tasks. These included: creating a story about their drawing while completing the Goodenough Harris Draw a Person Task, creating an original story with the opportunity to incorporate props; and completing the TELD- 3 receptive and expressive language task. We also recorded children's social and cognitive play behaviours using a modified version of Rubin's (2001) Play Observation Scale (POS). We found positive interactions between story creativity and play behaviours, story creativity and language, creativity (drawing) and language, creativity (drawing) and play behaviours, and play behaviours and language. These findings support the connection between creativity, language, and play and the benefits these skills and abilities have on children's learning and development.